IMPACT OF DIGITAL TECHNOLOGY ON THE ACCURACY AND RELIABILITY OF INFANT WEIGHT MEASUREMENTS GLOBALLY - Permana Sari, Fitriana Yuni; Setyonugroho, Winny (LPPM Universitas Duta Bangsa Surakarta, 2023)
The research aimed to investigate the influence of digital technology on the precision, dependability, and ubiquity of baby weight measurements on a global scale. This encompassed a variety of studies assessing the accuracy of hospital registers and self-reported data, obstacles and facilitators associated with weighing at delivery, the correlation between ultrasonography estimated foetal weight and birth weight, and the impact of quality improvement efforts on birth weight data. Additionally, indirectly related studies were considered, examining gestational weight gain, physical activity during pregnancy, infant anthropometry, and infant feeding practices. The findings indicate that while there remain challenges such as access to precise instruments and sufficient healthcare personnel, digital technology advancements, including digital health interventions, mobile-based solutions, and digital electrocardiograms, have significantly contributed to improving birth weight data accuracy and low birth weight prevalence. Furthermore, these advancements have also positively impacted other related aspects, such as gestational weight gain and community-based malnutrition screening, which indirectly influence newborn weight and overall infant and child well-being. Overall, despite existing challenges and areas requiring further research, digital technology advancements have significantly improved baby weight measurements' precision, reliability, and ubiquity worldwide, contributing to better neonatal and pediatric healthcare.